Ablation of the deubiquitinating enzyme cylindromatosis (CYLD) augments STAT1-mediated M1 macrophage polarization and fosters Staphylococcus aureus control - Schmidt, Christina; Harit, Kunjan; Traidl, Stephan; Naumann, Michael; Werfel, Thomas; Roesner, Lennart M.; Nishanth, Gopala; Schlüter, Dirk (Frontiers in Immunology, 2025)
In atopic dermatitis (AD), lesional skin is frequently colonized by Staphylococcus aureus, which promotes clinical symptoms of the disease. The inflammatory milieu in the skin is characterized by a Th2 response, including M2 macrophages, which cannot eradicate S. aureus. Therefore, repolarization of macrophages toward the M1 phenotype may foster control of S. aureus. Our data show that the deubiquitinating enzyme cylindromatosis (CYLD) is strongly expressed in macrophages of AD patients and prevents the clearance of S. aureus. Mechanistically, CYLD impaired M1 macrophage polarization by K63-specific deubiquitination of STAT1 and activation of the NF-κB pathway via its interaction with TRAF6, NEMO, and RIPK2. Inhibition of STAT1 and NF-κB, independently, abolished the differences between S. aureus-infected CYLD-deficient and CYLD-competent M1 macrophages. Infection of Cyld-deficient and wild-type mice with S. aureus confirmed the protective CYLD function. Collectively, our study shows that CYLD impairs the control of S. aureus in macrophages of AD patients, identifying CYLD as a potential therapeutic target.